Radiotracers for the Central Serotoninergic System - Reynald Mangeant; Emmanuelle Dubost; Thomas Cailly; Valérie Collot (MDPI AG, 2022)
This review lists the most important radiotracers described so far for imaging the central serotoninergic system. Single-photon emission computed tomography and positron emission tomography radiotracers are reviewed and critically discussed for each receptor.